2022
DOI: 10.1088/1361-6528/ac5e84
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride nanosheets supported highly homogeneous bimetallic AuPd alloy nanoparticles catalyst for hydrogen production from formic acid

Abstract: Formic acid (FA) has been recently regarded as a safe and stable source of hydrogen (H2). Selective and efficient dehydrogenation of FA by an effective catalyst under mild conditions is still a challenge. So, different molar ratios of bimetallic Pd-Au alloy nanoparticles were effectively stabilized and uniformly distributed on boron nitride nanosheets (BNSSs) surface via precipitation process. Obtained catalysts were employed in FA decomposition for H2 production. Pd-Au@BNNS containing 3% Au and 5% Pd (Au.03Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The activity of the WN/Gr PF samples is superior to that of the reported efficient non-precious metal catalysts (such as 1% Mo 2 C/Norit, 40 Mo 2 C-Co/GAC, 41 Mg 1.0 Mo 99.0 C 1− x , 42 Mo 2 C/Gr 43 and etc .) and also favorably comparable to that of some reported precious metal catalysts (such as Ni 0.4 Au 0.15 Pd 0.45 /C, 44 Ag–Pd core–shell nanocatalyst, 45 AuPd alloy nanoparticles catalyst, 46 2% Pd/ZnO 47 and etc .) These results suggest the promising application potential of W-based catalysts in the field of FA dehydrogenation.…”
Section: Resultssupporting
confidence: 87%
“…The activity of the WN/Gr PF samples is superior to that of the reported efficient non-precious metal catalysts (such as 1% Mo 2 C/Norit, 40 Mo 2 C-Co/GAC, 41 Mg 1.0 Mo 99.0 C 1− x , 42 Mo 2 C/Gr 43 and etc .) and also favorably comparable to that of some reported precious metal catalysts (such as Ni 0.4 Au 0.15 Pd 0.45 /C, 44 Ag–Pd core–shell nanocatalyst, 45 AuPd alloy nanoparticles catalyst, 46 2% Pd/ZnO 47 and etc .) These results suggest the promising application potential of W-based catalysts in the field of FA dehydrogenation.…”
Section: Resultssupporting
confidence: 87%
“…34 Chermahini and co-workers have demonstrated that hydroxyl-functionalized BN nanosheetsupported AuPd exhibits superior catalytic performance for FA dehydrogenation. 35 However, long reaction time, extra energy supply, or complex reaction steps are usually ineluctable during BN functionalization, and the agents employed for the treatment become inevitably unnecessary "contamination" in the resulting samples, 36 making them improper for supporting metal active sites in catalytic reactions. Therefore, it is desirable but challenging to develop a "clean" and effective approach to synthesize novel BN-NH 2 -supported AuPd NPs with hydrophilicity and excellent dispersion and superior catalytic performance for H 2 generation from FA dehydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To solve this problem, h-BN was modified by covalent or noncovalent functionalization schemes, including defect site derivatization, Lewis acid–base interaction, radical covalent functionalization, etc. For example, Huang and co-workers have introduced −NH 2 into porous boron nitride nanofibers to boost the H 2 generation from FA dehydrogenation of the AuPd catalyst . Chermahini and co-workers have demonstrated that hydroxyl-functionalized BN nanosheet-supported AuPd exhibits superior catalytic performance for FA dehydrogenation . However, long reaction time, extra energy supply, or complex reaction steps are usually ineluctable during BN functionalization, and the agents employed for the treatment become inevitably unnecessary “contamination” in the resulting samples, making them improper for supporting metal active sites in catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used catalysts for hydrogen production from formic acid are precious metals and composite catalysts with precious metal components [8,9]. Shaybanizadeh's team [10] stabled Pd-Au bimetallic alloy nanoparticles stabilized on boron nitride nanosheets via the deposition-precipitation method. When the catalyst contains 3% Pd and 5% Au, respectively, a hydrogen selectivity of 100% was reached at 50 • C. However, high costs and complex preparation processes limit the use of catalysts containing precious metals.…”
Section: Introductionmentioning
confidence: 99%